2017
DOI: 10.1101/140590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential associations of various depression-related phenotypes with cardiometabolic risks: Identification of shared genetic factors and implications for drug repositioning

Abstract: Depression and cardiometabolic diseases, such as coronary artery disease (CAD) and type 2 diabetes (DM), are commonly considered as risk factors to each other. However, little is known about the mechanism underlying the relationship between depression and cardiometabolic traits. Using a polygenic risk score approach, we investigated the genetic overlap of major depressive disorder (MDD) with various cardiometabolic traits based on summary statistics from large-scale meta-analyses of genome-wide association stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 162 publications
0
2
1
Order By: Relevance
“…Twin studies have previously shown genetic overlap between MDD and type 2 diabetes, but evidence from genetic studies has been weaker. The current study, however, does show evidence for a shared genetic aetiology between MDD and type 2 diabetes based on both polygenic risk scores and genetic correlations (21)(22)(23).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Twin studies have previously shown genetic overlap between MDD and type 2 diabetes, but evidence from genetic studies has been weaker. The current study, however, does show evidence for a shared genetic aetiology between MDD and type 2 diabetes based on both polygenic risk scores and genetic correlations (21)(22)(23).…”
Section: Discussioncontrasting
confidence: 83%
“…Studies using twin data also showed that the phenotypic association between MDD and type 2 diabetes was partly due to genetic effects (21). This finding has been replicated using a polygenic risk score approach(22), but not using genetic correlations (22,23). The Brainstorm Consortium did not find a significant genetic correlation between MDD and stroke(24), while Wassentheil-Smoller et al(25) showed that higher polygenic risk for MDD was associated with increased risk for stroke, in particular small vessel disease.…”
Section: However It Remains Unclear To What Extend These Mechanisms mentioning
confidence: 95%
“…Lamers et al, 2016, at 6-year follow-up only). In fact, genetic risk scores for severe melancholic depression seem to be associated with lower risk of adverse cardiac and metabolic symptoms (Wong et al, 2017).…”
Section: Example 3: Depressionmentioning
confidence: 99%